Fluvial Corridor'': A new ArcGIS toolbox package for multiscale riverscape exploration - Roux, Clément; Alber, Adrien; Bertrand, Mélanie; Vaudor, Lise; Piégay, Hervé (Geomorphology (Amsterdam, Netherlands), 2015)
Both for scientists and river basin managers, development of automated geographic information system (GIS) tools is essential today to characterize riverscapes and explore biogeomorphologic processes over large channel networks. Since the 1990s, GIS toolboxes and add-in programs have been used to characterize catchments. However, there is currently no equivalent to a planimetric and longitudinal characterization of fluvial corridor networks at multiple scales. This paper describes FluvialCorridor, a new GIS toolbox. This package allows the user: (i) to extract a large set of riverscape features such as the main components of fluvial corridors from DEM and vector layers (e.g. stream network or valley bottom), and (ii) to aggregate spatial features into homogeneous segments and metrics characterizing each of them. The methodological frameworks involved have been previously described by Alber and Piegay (2011), Leviandier et al. (2012) and Bertrand et al. (2013) and this contribution focuses on the GIS tools allowing the user to automatically operate them. A case study on the Drome River (France) is provided to illustrate the potential of the package both for geomorphologic understanding and target management actions. FluvialCorridor has been developed for ArcGIS with the related native Python library named ArcPy and tested on ArcGIS 10.0 and 10.1. Obviously, each component of the package can be used separately; however, it also provides a complete workflow for fluvial corridor characterization, even as the toolbox is continually under development and revision. Case study database, FluvialCorridor package and guidelines are available online at umrevs-isigfr. (C) 2014 Elsevier B.V. All rights reserved.